Physical models of loose soils dynamically marked by a moving object - Chanclou, B.; Luciani, A.; Habibi, A. (Proceedings Computer Animation '96, 1996)
The paper deals with the modeling of loose soil (sandy, muddy, etc.). When an object moves on such grounds, the object's and the soil's movement both depend on the mutual physical interactions, and therefore are very difficult to achieve with kinematic or geometric models. We use a particle based dynamic modeler and achieve a discrete model of plasticity, which accounts for the influence of the soil on objects moving on this soil, but also for the influence of the object on the movement and the shape of the soil. Thus we have simulated soil compression and piling, vehicles leaving tyre traces spinning, skidding and even sinking. This first step is the simulation of the soil object system at a discretization scale that can be termed "intermediate". A subsequent step consists of the simulation of a finer physical soil model in order to account for smaller scale dynamic phenomena.